2020
DOI: 10.1080/17435390.2020.1718232
|View full text |Cite
|
Sign up to set email alerts
|

Silicon dioxide and titanium dioxide particles found in human tissues

Abstract: Silicon dioxide (silica, SiO 2 , SAS) and titanium dioxide (TiO 2) are produced in high volumes and applied in many consumer and food products. As a consequence, there is a potential human exposure and subsequent systemic uptake of these particles. In this study we show the characterization and quantification of both total silicon (Si) and titanium (Ti), and particulate SiO 2 and TiO 2 in postmortem tissue samples from 15 deceased persons. Included tissues are liver, spleen, kidney and the intestinal tissues j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 40 publications
2
64
0
1
Order By: Relevance
“…The quantified Ti content in the human postmortem tissues from 15 individuals have been reported in a separate publication (Peters et al 2020). The findings confirmed the results from our previous study with human postmortem liver and spleen from 15 (other) individuals (Heringa et al 2018).…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…The quantified Ti content in the human postmortem tissues from 15 individuals have been reported in a separate publication (Peters et al 2020). The findings confirmed the results from our previous study with human postmortem liver and spleen from 15 (other) individuals (Heringa et al 2018).…”
Section: Introductionsupporting
confidence: 89%
“…In biological matrices, the concentration of TiO 2 is usually determined by quantifying the level of titanium (Ti). As is argued in Heringa et al (2018) and Peters et al (2020), it can be assumed that the Ti found in human tissues almost exclusively originate from oral exposure to TiO 2 particles. A potentially alternative source of Ti in organs (at least for internal organs) could come from corrosion of titanium implants, however, in the study by Heringa et al (2018) two donors with such implants did not have elevated Ti or Ti-particle levels in the internal organs analyzed (i.e.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations